2000
DOI: 10.1128/aem.66.4.1347-1353.2000
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Single-Reaction Multiplex PCR Toxin Typing Assay for Staphylococcus aureus Strains

Abstract: We describe here the development of a single-reaction multiplex PCR assay for the enterotoxin genes from Staphylococcus aureus that utilizes a universal toxin gene primer in combination with toxin-specific primers to amplify characteristic toxin gene products. In combination with a new DNA purification method, the assay can detect enterotoxin genes A to E from a pure culture within 3 to 4 h. The test was used to characterize a diverse set of environmental S. aureus isolates, and a 99% correlation with toxin ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 49 publications
2
82
0
6
Order By: Relevance
“…The surveillance of staphylococcal contamination within foods has been applied globally as critical tactic in public health. Sharma et al (35) reported that 41% of isolated S. aureus from milk bulk tank were capable of producing enterotoxin. In our investigation, only about 10% of staphylococcal isolates were positive for SEA.…”
Section: Discussionmentioning
confidence: 99%
“…The surveillance of staphylococcal contamination within foods has been applied globally as critical tactic in public health. Sharma et al (35) reported that 41% of isolated S. aureus from milk bulk tank were capable of producing enterotoxin. In our investigation, only about 10% of staphylococcal isolates were positive for SEA.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, methods for S. aureus toxin typing by multiplex PCR have been reported (6,26,29). These PCR methods are based on combinations of ent gene-specific primers or a combination of universal forward primers and specific reverse primers (36).…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques have been used to identify toxin genotypes, including DNA-DNA hybridization and PCR, but these protocols were designed to detect only one or a few toxin genes (21,35). Multiplex PCR for detection of several ent genes has been reported (6,26,29,30,36), but additional restriction endonuclease assays or other steps are required to ensure unambiguous identification of ent-specific amplicons. Therefore, there is still a need for a rapid and specific method for simultaneous detection and identification of SEs for diagnostic and epidemiological purposes.…”
mentioning
confidence: 99%
“…Para la identificación de las cepas de S. aureus por PCR, se amplificó una secuencia del gen de la nucleasa termoestable (nuc), con los cebadores descritos por primera vez por Brakstad, et al (9) (cuadro 1). Los oligonucleótidos cebadores empleados para identificar los genes de enterotoxinas (sea-see) fueron los propuestos por Sharma, et al (10). Este diseño permite, en una sola reacción de amplificación, la detección de genes que codifican estas enterotoxinas.…”
Section: Materiales Y Métodosunclassified